Evaluación del destino Puerto López que permita el desarrollo de un turismo sostenible - Maila Balderramo, Ronny Alejandro (2019)
The objective of this work was to carry out an evaluation in the Puerto López destination to allow the development of sustainable tourism, where an exploratory – descriptive research with a mixed approach was used. For the design of the methodology the review of several authors where considered in which 3 phases were established to achieve the objectives. The first phase consists of the selection of indicators in correlation with the availability of information on the territory, which requires 28 really useful indicators to comprehensively assess the destination. The second phase was based on a diagnosis that participated in a multidimensional characterization in contrast to the pillars of sustainability, so, with the review of official documents and field visits, the current situation of the place was known, then the offer and demand analysis was carried out through the application of tourist surveys and interviews with the GAD of Puerto López, in pursuit the tourist potentialities are analyzed with the use of methodology of Villegas and Sánchez (2000). The compilation of the previous data facilitates the evaluation of the space by means of indicators, determining that there are various circumstances that reduce tourism development, with the deficiency of basic services being the biggest problem. In the third phase, strategies and actions were formulated to mitigate the difficulties detected in the course of the investigation, thus, training, infrastructure adaptation, among other measures that would allow the proper management and use of study area were proposed.